INOVASI MASYARAKAT DESA WISATA CANDRAN DI ERA NEW NORMAL - Kiki Rizki Makiya; Shilfi Arizona (Kepariwisataan: Jurnal Ilmiah, 2021)
Innovation is an important factor that important to be noticed by the tourism village community to face tourism readiness in the era of new habits. Especially in the era of new habits, tourism destinations need to have a strategy as an effort to recover from the effects of the Covid19 pandemic. This research uses qualitative descriptive methodology with data collection techniques through secondary data collection and key informant interviews in Candran Tourism Village, Bantul. The study found that the community of the tourist village of Candran, Bantul, were aware of this. Therefore, they innovate by making agricultural fermentation activities for their livestock, as well as adding tourist attractions.Keywords: Inovation, Village Tourism, Agrotourism, New Normal Era